Iterated local search for the vehicle routing problem with a private fleet and a common carrier. Issue 10 (2nd October 2020) - Castaneda L., John F.; Toro, Eliana M.; Gallego R., Ramon A.
Abstract : A methodology is proposed that solves the vehicle routing problem with a private fleet and a common carrier using an iterated local search algorithm, based on two concepts: intensification and diversification. The first concept is implemented by using random variable neighbourhood search, while the second concept applies perturbation schemes. To validate the proposed methodology, systems with up to 50 customers and two to eight vehicles are tested. The results are compared with those presented in the specialized literature, including the quality of response and computation time, reaching in all cases the best solution reported with low computing times. In the second stage and given the previous verification, cases of medium and high mathematical complexity are analysed. These cases consider instances with 50 to 513 customers and 8 to 29 vehicles, and high-quality solutions are reached within reasonable computation times.